The relationship between emotional intelligence with student’s mathematics representation ability - Coesamin, M.; Sutiarso, Sugeng; Saputri, Nadila Intan (Technium Social Sciences Journal, 2021)
This study aims to determine the relationship between students’ emotional intelligence and students’ mathematical representation abilities. The population in the study were all eighth grade students of SMP Negeri 1 Sukoharjo, Sukoharjo sub-district, Pringsewu Regency for the 2020/2021 academic year which were distributed in nine classes. The research sample was selected by purposive sampling technique and 32 students were selected for class VIII-A. The design used is a correlational research design. The research data is in the form of quantitative data in the form of students’ emotional intelligence scores obtained through filling out questionnaires on students’ emotional intelligence and students’ mathematical representation ability scores obtained through circle material test activities. The data analysis technique in this study uses the Pearson product moment correlation test. The conclusion of this study is that there is a significant relationship between students’ emotional intelligence and students’ mathematical representation abilities, with a Pearson product moment correlation index number of 0.698, meaning that the higher the emotional intelligence of students, the higher the students’ mathematical representation ability.